2021
DOI: 10.3389/fphar.2021.622815
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective Effect of Sinapic Acid on Ethanol-Induced Gastric Ulcers in Rats: Involvement of Nrf2/HO-1 and NF-κB Signaling and Antiapoptotic Role

Abstract: Background: In the current study, we evaluated the therapeutic potential of sinapic acid (SA) in terms of the mechanism underlying its gastroprotective action against ethanol-induced gastric ulcers in rats.Methods: These effects were examined through gross macroscopic evaluation of the stomach cavity [gastric ulcer index (GUI)], alteration in pH, gastric juice volume, free acidity, total acidity, total gastric wall mucus, and changes in PGE2. In addition, we evaluated lipid peroxidation (malondialdehyde), anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 70 publications
(124 reference statements)
6
55
0
2
Order By: Relevance
“…The correlation between inflammation and the acidified ethanolinduced gastric ulcer model is well established (Raish et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between inflammation and the acidified ethanolinduced gastric ulcer model is well established (Raish et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were in line with those of previous studies indicating that 80% ethanol induces gastric ulcers by increasing ROS levels. The generation of high levels of ROS in gastric tissue plays a vital role in the formation of lipid peroxides, such as MDA, and is accompanied by antioxidative enzyme activity impairment in cells [ 42 , 43 ]. The results of the present study demonstrated that rats exposed to ethanol showed severe gastric lesions, increased free radical levels, and decreased levels of both antioxidative enzymes and non-enzymatic antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…(Lawson et al 1999). In rats with ethanol-induced ulcers, pretreatment with Sinapic Acid was found to decrease the acidity rate and reduce the stiffness of injuries in the gastric mucosa (Raish et al, 2021). Ellagic Acid taken into the body through food or dietary supplements has been shown to have the potential to be used in reducing intestinal in ammation (Iglesiasa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%